Photobiomodulation and Antimicrobial Photodynamic Therapy as Adjuvant Strategies in Medication-Related Osteonecrosis of the Jaws: A Narrative Review - Palma Suarez, Ramses B. (2025)
Medication-related osteonecrosis of the jaw (MRONJ) is a severe complication associated with antiresorptive and antiangiogenic therapies, characterized by persistent bone exposure, pain, and infection. Its multifactorial pathophysiology involves alterations in bone remodeling, angiogenesis, immune response, and local infection. In this context, light-based adjunctive strategies such as photobiomodulation therapy (PBM) and antimicrobial photodynamic therapy (aPDT) have emerged, showing promising outcomes in early stages of the disease. This narrative review examines the available scientific evidence on the use of PBM and aPDT in the prevention and treatment of MRONJ. A literature search was conducted in PubMed, Scopus, and Google Scholar up to April 2025. PBM acts by stimulating mitochondria and modulating inflammation, thereby enhancing wound healing and bone regeneration. aPDT combines localized antimicrobial effects with tissue biostimulation, proving effective in infected lesions resistant to antibiotics. Both therapies have demonstrated clinical benefits in early-stage MRONJ and in preventive settings, particularly when combined with minor surgical procedures and autologous biomaterials. Despite their potential, the current literature mainly consists of observational studies and case reports, which limits the strength of the evidence. Randomized controlled trials and standardized protocols are necessary to validate their routine use in clinical practice. PBM and aPDT represent safe, minimally invasive, and well-tolerated therapeutic options with relevant applications in patients at high risk of developing MRONJ or those with early-stage established disease.